Security and privacy in communication networks : 12th International Conference, SecureComm 2016, Guangzhou, China, October 10-12, 2016, Proceedings /: 12th International Conference, SecureComm 2016, Guangzhou, China, October 10-12, 2016, Proceedings. (2017) - Unknown
No abstract available